Unveiling the quaternary carbodiimide symphony: harmonizing green chemistry in peptide synthesis - Hlobisile Nzama; Srinivas Rao Manne; Oleg Marder; Gyorgy Orosz; Beatriz G. de la Torre; Fernando Albericio (Green Chemistry Letters and Reviews)
Although N-ethyl-N’-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC.HCl) is a common reagent in peptide synthesis, it presents two drawbacks. First of all, it is in a tautomerism equilibrium with cyclic form that it is not productive. Second, it is hydrolysed to the corresponding urea. Furthermore, it is only soluble in water, which limits its use in solid-phase peptide synthesis (SPPS) strategy. Herein, two quaternary carbodiimides (QCD), namely 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide methiodide (EDC.MeI) and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide methotosylate (EDC.MeTos), are described. The presence of the quaternary N prevents the formation of the cyclic form but preserves its solubility in water. However, the QCDs are also soluble in other organic solvents. These QCDs are totally stable at least up to 20 days. They present a level of racemization similar or even slightly better than EDC.HCl and a better performance when used for the Solid-Phase Peptide Synthesis (SPPS) of different peptides. Finally, the preliminary tests indicate that its use is safer than other carbodiimides.